Breast cancer - Liudmila G. Zhukova (IP Habib O.N., 2021)
Breast cancer (BC) is a malignant tumor originating from the epithelium of the breast tissue. There is no single etiological factor in the development of breast cancer. In 310% of patients with breast cancer, the development of the disease is associated with the presence of mutations in the breast cancer gene (BRCA) 1, BRCA2, CHEK, NBS1, TP53. In other patients, breast cancer is sporadic.